INTEGRATING INFORMATION SYSTEM SUCCESS MODEL (ISSM) AND TECHNOLOGY ACCEPTANCE MODEL (TAM): PROPOSING STUDENTS’ SATISFACTION WITH UNIVERSITY WEB PORTAL MODEL - Adeyemi, Ismail Olatunji; Issa, Abdulwahab Olanrewaju (Record and Library Journal, 2020)
Background of the study: The web portal is a tool that has been adopted by universities to manage data and information of students and faculty. The portal is an information system as it is driven by information.Purpose: The study proposes a model of students? satisfaction with Web portal for the integration of Information System Success Model ISSM and Davis? Technology Acceptance Model (TAM).Method: The methodology adopted for this study is the critical review of literature that borders on the constructs and/or variables embedded in ISSM and TAM.Findings: The study theorizes that information quality, service quality and system quality and perceived usefulness individually determine students? satisfaction of a Web portal. The study also predicts that all of these variables compositely determine the students? satisfaction of university Web.Conclusion: The study established that the ?mandatory use? of Web portal does not primarily translate to students? satisfaction with the portal. This is because whether users are satisfied or not, the onus is still on them to come back to use the portal.